Sandy Dennis the life and films - Shelley, Peter 1962- (McFarland, 2014)
"A study of the American actress Sandy Dennis (1937-1992), winner of Tony Awards for her work in the theatre in 1963 and 1964, she moved into film. For her performance in Who's Afraid of Virginia Woolf? (1966) Dennis won the Best Supporting Actress Academy Award. Full information is provided for her films and television appearances"..
Includes bibliographical references and index
Keywords: Farmer, Frances, -- 1913-1970; Dennis, Sandy -- 1937-1992; Actors -- United States -- Biography; Motion picture actors and actresses -- United States -- Biography; USA; Biografie